Genetic Factors in Acute Myeloid Leukemia With Myelodysplasia-Related Changes: A Study of 186 Cases. Issue 5 (16th January 2020) - Fang, Hong; He, Rong; Chiu, April; Viswanatha, David S; Ketterling, Rhett P; Patnaik, Mrinal S; Reichard, Kaaren K
Abstract: Objectives: Acute myeloid leukemia with myelodysplasia-related changes (AML-MRC) is a heterogeneous category with a broad range of underlying genetic abnormalities. We investigated the significance of genetic factors in a large series of AML-MRC cases. Methods: The morphologic findings, genetic data, and patient outcomes were assessed in 186 AML-MRC cases. Results: The median overall survival (OS) was dismal in AML-MRC patients (median, 7.6 months; 95% confidence interval, 5-10.6 months). Karyotypically normal cases and cytogenetically abnormal cases without myelodysplastic syndrome (MDS)-related cytogenetic abnormalities showed similar OS, significantly better than cases carrying MDS-related cytogenetic abnormalities. MDS-related cytogenetic abnormalities, monosomal or complex karyotype, and history of MDS or myelodysplastic/myeloproliferative neoplasm were all associated with dismal outcome. Conclusions: AML-MRC predicts a poor prognosis. Our study supports the finding that the genetic profile plays a key role in determining prognosis in AML-MRC as defined according to the World Health Organization revised fourth edition (2017) diagnostic criteria.